Traumatic Healing Program for Elementary School Student in Sumberdadi Village Post Online Learning During Pandemic Covid-19 - Nanda William; Wawan Prasetyo; Wilujeng Dewi Latiifah Hasan; Nina Nur Fitriyah; Tansi Avrelia Rekalasdiana (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2022)
Pandemic covid 19 has brought about big impact to all sectors including education. The online learning during pandemic brought great impact to the psychology of the elementary school student. In addition, it also changed the student habit. The government policy to conduct limited offline meeting can not make students directly go to school and receive the material from the teacher. This psychological condition must be prepared so that the students can and enjoy and follow the learning maximally. This preparation is made through traumatic healing program in the form of fun learning which can boost student’s literacy, sport and skill. This program used service-learning method and involved students and Sumberdadi people as well. The target of this program is elementary school student from Sumberdadi village. This program was held for two months. The result of this program showed that students were enthusiastic and full of spirit to join the program. Besides, the no longer complained about the activity of doing assignment from schools. It can be concluded that the students are ready to join limited offline meeting at school